2015
DOI: 10.1007/s13277-015-4460-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical implication of S100A12 in gastric carcinoma

Abstract: S100 protein family has been implicated in multiple stages of tumorigenesis and progression in which S100A12 is one of the subtypes. However, the role of S100A12 in gastric carcinoma (GC) has not been elucidated yet. This study was aimed to investigate the expression of S100A12 in GC tissues and evaluate the clinical significance of S100A12 in GC patients. S100A12 protein was detected in 207 GC and 52 paired non-cancerous mucosal tissues by immunohistochemistry, while messenger RNA (mRNA) was investigated by O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…USP10, S100A12, p53, and Ki67 are tumor molecular markers for cancer invasion and metastasis . USP10 is a de‐ubiquitination enzyme, which removes ubiquitin from specific protein substrates, allowing protein salvage from proteasome degradation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…USP10, S100A12, p53, and Ki67 are tumor molecular markers for cancer invasion and metastasis . USP10 is a de‐ubiquitination enzyme, which removes ubiquitin from specific protein substrates, allowing protein salvage from proteasome degradation .…”
Section: Discussionmentioning
confidence: 99%
“…found that TM4SF1 was ubiquitylated and that ubiquitylation was essential for its function in cell migration . Our previous study indicated that S100A12 expression was correlated with the depth of invasion, and it was evaluated as an independent risk factor for poor overall survival of GC . p53 and Ki67 are established markers for cancer progression .…”
Section: Discussionmentioning
confidence: 99%
“…Comparing noncancerous gastric mucosa and tumor tissue, S100A12 was expressed in gastric epithelial cell lines and stromal cells (i.e., monocytes, lymphocytes, and neutrophils) in both conditions [51,52]. The staining pattern showed stronger signal in stromal cells on cases and controls, with the nucleus and cytoplasm being clearly visible in stromal lines while only the cytoplasm stained positive in epithelial cells [51]. However, S100A12 expression was reduced in gastric cancer epithelia when compared to noncancerous gastric epithelial cells [52].…”
Section: Resultsmentioning
confidence: 99%
“…With these results, the authors suggest that calgranulin C may serve as a novel prognostic marker for detecting aggressive GC. Further research is needed to explore whether S100A12 has protective roles in tumorigenesis and how those mechanisms may operate [51,52]. H. pylori infection is the single biggest risk factor associated with gastric cancer, and gastritis is a critical process in the precancerous signaling cascade [53,54].…”
Section: Resultsmentioning
confidence: 99%
“…The human S100A12 protein is overexpressed in several tissues in conditions such as gastric carcinoma, diabetes, Crohn’s disease, and Mooren’s ulcer. These diseases are usually related to the inflammation of cells [6–9]. The S100A12 protein expresses its bio-activity after calcium ions bind to its EF-hand domains [1012].…”
Section: Introductionmentioning
confidence: 99%